Análise do consumo energético de um sistema de extração de óleo de macaúba - Rosária Ferreira da Silva (2023)
The macaúba (Acrocomia aculeata) is a native palm tree of America tropical regions and it is a promising species for exploitation due to the high productivity of oil and by-products possible to obtain through the processing of its fruit. Once the importance of macaúba oil is evidenced, it is necessary to evaluate the existing extraction methods in order to obtain the best energy use throughout the process. In this context, the main objective of this study was to perform an analysis of the energy consumption of a macaúba oil extraction system based on the development of a conceptual plant based on experimental data and data from the literature. An overview of the cultivation and processing of the species for various purposes was also presented. For this study, the first step consisted of delimiting the system to be analyzed and all the inherent variables; to this end, the information obtained from a pilot plant installed at the Federal University of Viçosa (UFV), in Minas Gerais, was combined with the data available in the literature. For the energy evaluation, the production/consumption ratio between energy inputs and outputs was considered, identifying the values of the expenditures used in the extraction of macaúba oil and by-products in terms of useful energy. Representative diagrams were prepared for each step of the process. For the input data, considerations were made and the terms of operation of each equipment used in the process were defined and then the demand for electrical energy required for each step was determined. The energy outputs were defined based on the upper and lower calorific value of the by-products obtained. Therefore, the energy consumption of each isolated step and of the system as a whole was obtained. It was considered the processing of 300 kg in a time of 134.26 hours, estimated the total expenditure of 4,574.71 kWh in electricity, and it was obtained a final production of 1,152.95 kWh (according to the calorific value of the products obtained). It is concluded that for the consolidation of a sustainable production chain it is necessary to improve the extraction process, since it presented high energy consumption. It was observed that among the stages of the extraction process the most expensive step from the energy point of view is drying and that improving it is fundamental to increase efficiency and obtain the conscious use of the energy resources used in the process of extraction of macaúba oil.